2013
DOI: 10.1002/jgrf.20153
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effect of tree uprooting on variation of soil horizon depth by confronting pedogenetic simulations to measurements in a Belgian loess area

Abstract: [1] Spatial patterns of soil often do not reflect those of topographic controls. We attempted to identify possible causes of this by comparing observed and simulated soil horizon depths. Observed depths of E, Bt, BC, C1, and C2 horizons in loess-derived soils in Belgium showed a weak to absent relation to terrain attributes in a sloping area. We applied the soil genesis model SoilGen2.16 onto 108 1 × 1 m 2 locations in a 1329 ha area to find possible causes. Two scenarios were simulated. Model 1 simulated soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 59 publications
(109 reference statements)
0
17
3
Order By: Relevance
“…Indeed, slope position and exposure have implications on the process of soil formation in loess areas (Finke, 2012;Finke et al, 2013). On a microscale level this fact has implications on soil development and on the degree of surface vegetation cover.…”
Section: Site-specific Controls On Sedimentological Processesmentioning
confidence: 99%
“…Indeed, slope position and exposure have implications on the process of soil formation in loess areas (Finke, 2012;Finke et al, 2013). On a microscale level this fact has implications on soil development and on the degree of surface vegetation cover.…”
Section: Site-specific Controls On Sedimentological Processesmentioning
confidence: 99%
“…A literature scan of 29 published articles (Kirkby, 1977(Kirkby, , 1985Hoosbeek and Bryant, 1994;Dietrich et al, 1995;Minasny and McBratney, 1999, 2006Van Oost et al, 2003;Rasmussen et al, 2005;Follain et al, 2006;Goddéris et al, 2006Goddéris et al, , 2010Rosenbloom et al, 2006;Saco et al, 2006a;Rasmussen and Tabor, 2007;Salvador-Blanes et al, 2007;Brantley et al, 2008;Finke and Hutson, 2008;Jacques et al, 2008;Sommer et al, 2008;Cohen et al, 2010;Hirmas et al, 2010;Baartman et al, 2012;Finke, 2012a;Sauer et al, 2012;Finke et al, 2013;Vanwalleghem et al, 2013;Yu et al, 2013;Zwertvaegher et al, 2013b) on case studies of pedogenetic soil models at the profile scale as well as the landscape scale was done to check process coverage according to Table 3. The scan revealed that process coverage is higher for soil profile models than for landscape models, but is still incomplete (Fig.…”
Section: Process Coveragementioning
confidence: 99%
“…In that case, profile models can be applied at multiple locations representing the area, and simulated soil property profiles at a desired time can be interpolated. Finke et al (2013) give an example of deep loess soils where point simulations were used to investigate patterns of horizon thickness by regression kriging.…”
Section: Soilscape Genesis By Distributed Profile Modelingmentioning
confidence: 99%
“…The way forward is to examine the problem in various locations with different place and history factors. Several studies in a variety of environments provide partial support –either they confirm the operation of key processes or mechanisms, or present findings with respect to tree–soil thickness relationships consistent with the conceptual model (Gabet and Mudd, ; Roering et al ., ; Finke et al ., ; Pawlik et al . , ; Nie et al ., ).…”
Section: Introductionmentioning
confidence: 99%